The Validity of Land Ownership Granted by Fellow Indonesian Citizens Based on a Name-Loan Agreement (Case Study at the Sharia Savings and Loans Cooperative and Financing Baitul Maal Wat Tamwil Dinar Rahmat Insani Muamalat, Tegal Regency) - Ani, Nafa; Witasari, Aryani (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
This research aims to analyze the legal validity of land ownership based on nominee agreements between Indonesian citizens, with a case study at KSPS BMT DRI Muamalat in Tegal Regency. Nominee agreements, although not explicitly regulated in the Indonesian Civil Code (KUHPerdata), are commonly practiced to circumvent legal restrictions on land ownership. This study uses a normative juridical approach with descriptive-analytical specifications. Data were collected through literature studies and interviews, then analyzed qualitatively. The findings show that nominee agreements may lead to legal uncertainty and violate the principle of good faith, especially when used to conceal actual ownership. Notaries involved in such agreements remain responsible for ensuring that the legal documents they prepare comply with prevailing laws and do not facilitate unlawful arrangements.